Primary Angiosarcoma of the Spleen: Rare Diagnosis with Atypical Clinical Course - Filip Kohutek; Ladislav Badik; Branislav Bystricky (Case Reports in Oncological Medicine)
Primary angiosarcoma of the spleen is a rare diagnosis with poor prognosis. Morphologically, it demonstrates conventional blood vessel differentiation. We present a case of 65-year-old female who underwent radical splenectomy for primary angiosarcoma of the spleen. After three-year disease-free interval, she was diagnosed with bone-only metastatic disease. Palliative radiotherapy and bisphosphonates kept her disease reasonably stable for another four years. After development of lung metastases, six cycles of single agent doxorubicin kept her progression-free for six years. Upon further progression in lungs, thirteen years after original diagnosis, lung biopsy confirmed metastatic splenic angiosarcoma in the lungs. She started weekly paclitaxel chemotherapy. Although splenic angiosarcoma generally carries grave prognosis, some patients may enjoy prolonged periods of disease stabilization. Durable benefit can be achieved in some patients with multimodality management. We review the literature focusing on systemic treatment for this rare tumor.